FAKTOR PENENTU PEMBERIAN ASI EKSKLUSIF PADA PENGGUNA KONTRASEPSI HORMONAL DAN NON HORMONAL - , WIDANINGSIH; , Prof. dr. Siswanto Agus Wilopo, SU, MSc., Sc.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The program of exclusive breastfeeding has been initiated for 20 years, but the target of 80% is difficult to achieve. Data of Basic Health Research (Riskesdas) 2007 showed that coverage of exclusive breastfeeding in Indonesia was 15.3%, and in 2010 the coverage was 27.2%. It is assumed that low coverage of exclusive breastfeeding supplementation is caused by change in breastfeeding pattern. Based on the result of umbrella research, coverage of exclusive breastfeeding was 44.3%. Use of post partum contraception is still relatively low due to lack of awareness and information obtained by the community particularly postpartum mothers that leads to misunderstood information on contraception device. In one side the community believes that breastfeeding pattern is closely associated with sustainability of exclusive breastfeeding. Objective: To identify behavior and factors determining exclusive breastfeeding supplementation in postpartum mothers acceptors of hormonal and non hormonal contraception. Method: This was a qualitative study with ethnographic design and observation technique. Data were obtained through non structured in-depth interview and through observation on behavior of mothers acceptors of hormonal and non hormonal contraception in breastfeeding infants from birth to the period when the infants were introduced to complementary breastfeeding maximum at the age of 6 months holistic. Result: Factors affecting exclusive breastfeeding supplementation were: 1) factor of the baby /whining, refuses the nipple